A Review of Water Resources Education in Geography Departments in the United States. (11th January 2020) - Pease, Mike; Chaney, Philip L.; Hoover, Joseph
Abstract: Geographers have long played an important role in water resources scholarship; however, academic literature has not focused on the teaching contributions of geographers in this area. To address this gap, we cataloged courses taught and faculty interests for geography departments in the United States with a stated focus on water resources. We identified 129 departments with both courses and faculty having water resources expertise. The majority of water‐related courses focused on climatology or climate change, suggesting that students are regularly provided opportunities to learn about water topics primarily through the lens of climatology and water resources. We also summarize a panel organized at the 2017 American Association of Geographers Annual Conference that focused on water resources curriculum in geography programs. The panel discussed curriculum and pedagogical approaches, concluding that a water resources course syllabi repository would be beneficial for creating new and refining existing water resources courses. The panel also recommended that faculty consider incorporating water resources topics into their general education classes to concurrently enhance student learning opportunities and positively impact recruitment and interest in geography programs. Additionally, online education represents a substantial change in higher education that presents new challenges and opportunities for geographers. We hope these data and the summary of the panel session stimulate greater discussions of curricular needs across all disciplines that offer water resource focused courses.